Eksfoliasi Bahasa Kekuasaan dalam Paradigma Komunikasi Verbal - Vrestanti Novalia Santosa (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
Language is closely related to the communication process, both spoken and written verbal communication. Its application is symbolic, so it needs to be interpreted carefully based on several considerations, including the communication context, the background of the message recipient, the form of communication, the type of communication, and language attitudes. Language does not only reflect social status, but can be used as a symbol that shows and maintains power, acceptance and recognition of the authority given by society to stakeholders who have been given power. Legitimacy is formed through a community that has shared desires and goals in the form of power with the main source of legitimacy being tradition, charisma and rational instruments. This is the impetus for research on exfoliating the language of power from a verbal communication perspective. The problem raised in this research is the form of symbols for exfoliating the language of power in the oral and written communication paradigm, as well as the function and meaning of the language of power in the verbal communication paradigm. This type of qualitative research is descriptive with a literature study and field study approach according to the social reality of society. It is hoped that this research can raise people's critical awareness of the language of power and develop humanist verbal communication, namely verbal communication that realizes equal human dignity. Public awareness of evolutionary verbal communication can break the chain of verbal violence that occurs in society.